KILAS BALIK PENDIDIKAN NU DI BALIK TABIR GURU PARA KYAI - Syaiful Hadi Pulungan; Fathurrahman Fathurrahman (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
The Nahdlatul Ulama (NU) organization is a community organization that focuses on several fields, such as education, social and political. The Nahdlatul Ulama mass organization adheres to the Ahlussunnah Wal Jama'ah (Aswaja) ideology, in which the Aswaja ideology is an understanding that adheres to five sources of law. This paper aims to review the development of Nahdlatul Ulama education in the archipelago to raise the figure of a charismatic scholar, KH. Hasyim Asy'ari (1871-9147). This writing methodology uses library research research with a descriptive approach. The results of this study explain the dynamics of Nahlatul Ulama education to prove that education today is a benchmark for the pioneering education of the colonial era. And the NU organization has great attention to the education sector. Of course, we can see this together from the number of pesantren and madrasas managed by Nahdlatul Ulama (NU). In formal education and teaching, NU established the al-Ma'arif institution